Isomaltooligosaccharide increases the Lactobacillus rhamnosus viable count in Cheddar cheese. (18th March 2015) - Liu, Lu; Li, Xiaodong; Bi, Weiwei; Zhang, Ling; Ma, Liyuan; Ren, Hongjing; Li, Minghao
<x xml:space="preserve">Abstract</x> Five batches of Cheddar cheese were manufactured containing different levels of isomaltooligosaccharide (IMO) and a probiotic strain of Lactobacillus rhamnosus to study the effect of IMO on the survival of starter lactococci and probiotic micro‐organisms, on proteolytic patterns, cheese composition and sensory properties. The cheese was exposed to conditions simulating those found in the gastrointestinal tract to evaluate the survival of Lb. rhamnosus. Results demonstrated that the addition of Lb. rhamnosus and IMO did not affect the main compositional variables of Cheddar cheese. The counts of starter culture and probiotic organisms increased in cheese which contained Isomaltooligosaccharide (Batches 3, 4 and 5) more than in the control (Batches 1 and 2) during the fermentation. The probiotic counts in fresh cheese (B‐4) was 9.23 log10 cfu/g which was more than one log cycle greater than in the control (B‐2). The probiotic counts remained above 8 log10 cfu/g at the end of the manufacturing process. Primary proteolysis was not affected by the addition of probiotic bacteria and IMO, but the level of secondary proteolysis was slightly higher compared with the control group. The addition of IMO improved the texture and sensory quality of the cheese and the probiotic bacterium had the same effect. Under conditions that simulated the gastrointestinal tract, the probiotic bacteria in cheese (B‐4) exhibited good survival and remained above the recommended 6–7 log10 cfu/g.